Peran Pola Asuh dan Stimulasi Orang Tua Terhadap Risiko Speech Delay Pada Anak - Astuti, Titi; Aprina, Aprina; Anita, Anita (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Speech delay in children is a developmental disorder that can affect communication skills, learning processes, and social interactions. Parental parenting and stimulation are environmental factors that play an important role in children's speech development, the Lampung Provincial Health Office report reported 24 children with developmental disorders; Among them, 7 children (29.16%) were in the speech domain. To determine the role of parenting and parental stimulation on the risk of speech delay in preschool-age children. A type of quantitative research with an analytical design of a cross-sectional approach. The population is all pre-school age children with a research sample of 200 pre-school children selected by purposive sampling technique. The independent variables are parental parenting (democratic, authoritarian, permissive) and parental stimulation (good, enough, less), while the dependent variable is the incidence of speech delay. Data collection was carried out using questionnaires and observation sheets. Data analysis used Chi-Square test and logistic regression. The results of the parenting study were mostly authoritarian (53.0%), the stimulation of parents was mostly in the good category (53.5%), and the results showed that there was a significant relationship between parenting and the incidence of speech delay (p = 0.000; OR = 20.620), as well as between parental stimulation and the incidence of speech delay (p = 0.000; OR = 20.462). Children with authoritarian and less stimulated parenting have a higher risk of speech delay compared to children who are democratically raised and receive adequate stimulation. Parenting and parental stimulation play a significant role in the risk of speech delay in preschool-age children. Parents are expected to implement positive parenting and provide consistent stimulation to optimize children's speech development. Keywords: Parenting Style, Parental Stimulation, Speech Delay, Preschool Children.  ABSTRAK Speech delay pada anak merupakan gangguan perkembangan yang dapat memengaruhi kemampuan komunikasi, proses belajar, dan interaksi sosial. Pola asuh dan stimulasi orang tua merupakan faktor lingkungan yang berperan penting dalam perkembangan bicara anak, Laporan Dinas Kesehatan Provinsi Lampung dilaporkan 24 anak dengan gangguan perkembangan; di antaranya 7 anak (29,16%) pada domain bicara. Mengetahui peran pola asuh dan stimulasi orang tua terhadap risiko speech delay pada anak usia pra sekolah. Jenis penelitian kuantitatif dengan desain analitik pendekatan cross-sectional. Populasi adalah seluruh anak usia pra sekolah dengan Sampel penelitian berjumlah 200 anak usia pra sekolah yang dipilih dengan teknik purposive sampling. Variabel independen adalah pola asuh orang tua (demokratis, otoriter, permisif) dan stimulasi orang tua (baik, cukup, kurang), sedangkan variabel dependen adalah kejadian speech delay. Pengumpulan data dilakukan menggunakan kuesioner dan lembar observasi. Analisis data menggunakan uji Chi-Square dan regresi logistik. Hasil penelitian pola asuh orang tua sebagian besar bersifat otoriter (53,0%), Stimulasi orang tua mayoritas dalam kategori baik (53,5%), dan hasil menunjukkan terdapat hubungan yang signifikan antara pola asuh dengan kejadian speech delay (p = 0,000; OR = 20,620), serta antara stimulasi orang tua dengan kejadian speech delay (p = 0,000; OR = 20,462). Anak dengan pola asuh otoriter dan stimulasi yang kurang memiliki risiko lebih tinggi mengalami speech delay dibandingkan dengan anak yang diasuh secara demokratis dan mendapat stimulasi yang adekuat. Pola asuh dan stimulasi orang tua berperan signifikan terhadap risiko speech delaypada anak usia pra sekolah. Orang tua diharapkan menerapkan pola asuh positif dan memberikan stimulasi yang konsisten untuk mengoptimalkan perkembangan bicara anak. Kata Kunci: Pola Asuh, Stimulasi Orang Tua, Speech Delay, Anak Pra Sekolah